Magnesium Alloys Structure and Properties - Tański, Tomasz; Jarka, Paweł (IntechOpen, 2022)
Magnesium Alloys Structure and Properties is a comprehensive overview of the latest knowledge in the field of magnesium alloys engineering. Modern magnesium alloys are promising for a variety of applications in many branches of the industry due to their excellent mechanical properties, high vibration, damping capacity, and high dimensional stability. This book discusses the production, processing, and application of magnesium alloys. It includes detailed information on the impact of alloying additives and selected casting technologies, as well as modern manufacturing technologies based on powder metallurgy, the production of composites and nano-composites with metal matrixes, and methods for improving alloy properties.